Manajemen Ekstrakurikuler Drumband di Sekolah Dasar - Okta Rizkika Ramadhona; Lungit Wicaksono; Amrina Izzatika; Ari Sofia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The problem addressed in this research is the difference in drumband achievement outcomes between SDN X and SDN Y, indicating variations in the implementation of extracurricular management functions. The purpose of this research is to know the management activity of the drum band extracurricular at SDN X and SDN Y. The method used in this research is descriptive quantitative with a case study research design. Data were collected by interview, observation, and documentation, with a total of 5 informants, including the school principal, supervisor, trainer, and students of the drumband extracurricular. Data were analyzed by data condensation, data presentation, and conclusion. The results showed that 1. The drumband activity planning is carried out through the formulation of a structured training program, systematic scheduling, and the clear activity objectives. However, SDN X has a more structured planning framework. 2. The organization at SDN X operates more cleary through a well-coordinated division of tasks, while at SDN Y limitations in coordination were identified. 3. The implementation of activities at SDN X is carried out more optimally and consistently, while SDN Y still faces limitations in facilities. 4. Monitoring is conducted through the observation of training sessions and the activity evaluation. 5. Supporting factors include students’ enthusiasm, the competence of the trainer, and support from the school principal. For the inhibiting factors, there are the limitation of facilities and the weather conditions.